PENGARUH KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA INDUSTRI TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2012-2016 - Retno P, Dwi; R. Pandin, Maria Yovita (Universitas 17 Agustus 1945 Surabaya, 2020)
ABSTRACTThis study has the aim of knowing the effect of dividend policy as measured by dividends per share and dividend payout ratio on stock prices. This research is quantitative descriptive. The total companies that will be studied are 3 companies which are determined through purposive sampling. In this study shows the results that dividend policy does not have a significant effect on the stock prices of textile and garment companies listed on the Indonesia Stock Exchange (IDX). While simultaneously dividends per share and dividend payout ratio have no effect on stock prices. This shows that dividends do not provide signals or information to investors to invest in shares, because investors feel the same, whether they receive dividends at present or not, in the end investors will invest again and the rise and fall of the DPR will not affect investors whether will invest in the company or not.